Enhancing the islamic microfinance to overcome riba based economy - Abdulsoma, Thoarlim (2016)
In order to have the success of economic policies to develop microenterprises and alleviate the problems of poverty in Indonesia over the past two decades, financing microenterprises was considered as a new paradigm in the grass root economic sector and became the popular subject of study by a number of researchers in the past, particularly, after the proclamation of the year 2005 as the microfinance year by the United Nations (NU) and labeling Mohammed Yunus - founder of Grameen Bank of Bangladesh- as the pioneer of microfinance. Moreover, the innovative poverty eradication and economic development policies of Grameen Bank focused on solidarity group-based financing scheme was considered as a new concept and has burgeoned in both developing and industrialized countries, including Muslim countries. However, this success has been criticized by some Muslim researchers; they said that financing and services offered by microfinance institutions are based on interest (riba) and some other prohibited elements. Most of their social development programs are secular in nature. Therefore, the discussion begins with the characteristics and structure of microfinance, historical development of microfinance followed by the discussion on inclusiveness of Islamic microfinance. Some important issues closely related to the subject are also discussed. These issues include the foundations of Islamic microfinance, Shariah compliance of contract and comparative analysis of the conventional microfinance system from the Shariah perspective.